2001
DOI: 10.1053/gast.2001.29673
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis gene mutations and pancreatitis risk: Relation to epithelial ion transport and trypsin inhibitor gene mutations

Abstract: CFTR-related pancreatitis risk correlates with having 2 CFTR mutations and reduced extrapancreatic CFTR function. The N34S PSTI mutation increased risk separately. Testing for pancreatitis-associated CFTR and PSTI genotypes may be useful in nonalcoholic pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
161
2
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(178 citation statements)
references
References 52 publications
10
161
2
5
Order By: Relevance
“…This frequency is higher than the 4.3% 20 and 5.0%, 31 similar to the 9.4%, 19 but much lower than the 18.8%, 7 23.1%, 28 25.9%, 16 and 28.6%, 18 reported in other studies. This discrepancy may be mainly due to the difference in the composition of patients chosen in these studies.…”
contrasting
confidence: 46%
See 2 more Smart Citations
“…This frequency is higher than the 4.3% 20 and 5.0%, 31 similar to the 9.4%, 19 but much lower than the 18.8%, 7 23.1%, 28 25.9%, 16 and 28.6%, 18 reported in other studies. This discrepancy may be mainly due to the difference in the composition of patients chosen in these studies.…”
contrasting
confidence: 46%
“…In this regard, it is important to note that the same R122H mutation was also detected in one out of 39 well-characterised ICP patients in a just published study. 28 Moreover, this mutation was found in a patient diagnosed for 20 years as having alcoholic pancreatitis and with no family history of pancreatic disease. 29 Furthermore, a gene conversion event, a c.365*366GC4AT two base pair nucleotide change, which also results in a R122H mutation in PRSS1, was also detected in one Belgian with ICP.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The latter is an idiopathic, juvenile, nonalcoholic form of CP widely prevalent in several tropical countries. By simultaneously analyzing 39 ICP subjects for common mutations of CFTR, SPINK1, and PRSS1, Noone et al 31 found that about 60% of their patients had at least one mutation in either CFTR or SPINK1, or both. Interestingly, the risk of pancreatitis was increased approximately fivefold by having one CFTR mutation, 20-fold by having SPINK1 N34S mutation, 40-fold by having two CFTR mutations (compound heterozygotes), and 900-fold by having N34S and two CFTR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Noone et al [53] revealed association of CFTR mutations with ICP and a possibility of its interaction with PRSS1 and SPINK1 mutations in western populations. However, the frequency of CFTR mutations was found to be lower in TCP patients [54] , and needs to be studied in a larger group of patients.…”
Section: Genetics Of Tcpmentioning
confidence: 99%